Vers une meilleure compréhension de la persévérance et de la réussite académique : analyse critique de ces concepts adaptée au contexte belge francophone - Nathalie Roland; Mikaël De Clercq; Serge Dupont; Philippe Parmentier; Mariane Frenay (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
Academic achievement and Persistence have been extensively studied among researchers in psychology and education sciences. However, despite a vast literature on the subject, these two concepts are not always clearly defined. In addition, there is a lack of consensus about the conceptualization and the operationalization of these concepts. The purpose of this theoretical article is to point out the current limitations of the literature on the conceptualization and operationalization of these two concepts and to expose the consequences. Then we will develop a rigorous conceptualization and operationalization of these concepts in the francophone Belgian context. We will also discuss the relationship between Persistence and Achievement, the interest of their promotion in the Belgian educational system and the implications of our thinking about future research in the field.